A double blind randomised trial of low power laser treatment in rheumatoid arthritis. Issue 10 (October 1993) - Heussler, J K; Hinchey, G; Margiotta, E; Quinn, R; Butler, P; Martin, J; Sturgess, A D
Abstract : OBJECTIVES–To define the value of low power laser treatment in small joint rheumatoid arthritis. METHODS–Twenty five women with active disease were recruited. The metacarpophalangeal and proximal interphalangeal joints of one hand were treated with 12 J/cm2 for 30 s with a gallium-aluminium-arsenate laser. The other hand received a sham laser treatment designed so that neither therapist nor patient could distinguish the active laser from the sham laser. Each patient received 12 treatments over four weeks. The following parameters were measured: pain as assessed by visual analogue scale; range of joint movements; grip strength; duration of early morning stiffness, joint circumference, Jebsen's hand assessment; drug usage; total swollen joint counts; Arthritis Impact Measurement Scales; three phase bone scans; haematological and serological tests. RESULTS–A total of 72% of patients reported pain relief but this reduction was reported equally in both hands. No significant changes were seen in other clinical, functional, scintigraphic, or laboratory features. Neither patients nor staff were able to detect which hand was treated with the active laser. CONCLUSION–When this specific laser and dose regimen was used, low power laser treatment had no objective effect on patients with rheumatoid arthritis. It did appear to produce analgesia through a powerful placebo effect.